The Ransom of Red Chief - Henry, O., 1862-1910; Retold by Shipton, Paul and Illustrated by Rator, Axel (Oxford, New York Oxford University Press, 2008)
Word count 890 Suitable for young learners
Include Color Illustration
Keywords: Kidnapping -- Humorous stories -- Children's literature